Students' motivations and actions when they learn mathematics using CAS : a study using an activity theory approach. - Periasamy, Jeevasundarie (My University, 2012)
I explore students‟ motivations towards using Computer Algebra Systems (CAS) in learning mathematics, their associated actions and the relationship between their motivations and actions. Leontiev‟s (1978) philosophy of needs, motives and goals provides a powerful theory within which to understand students‟ motivations and actions in a learning context mediated by tools, thus the study is located within the framework of Leontiev‟s activity theory. It draws particularly on his notions of activity, actions and operations, as well as on Western motivational concepts of achievement goal theory and expectancy-value theory. Specifically, the notions of mastery approach goal-orientations, performance approach goal-orientations and social goal-orientations are examined, as are task value components (comprising „importance‟ of task, intrinsic reasons and extrinsic utility value). I also discuss indexes of motivation, which comprise choice of tasks, effort and persistence. An important theoretical contribution of this thesis lies in the elaboration of the aforementioned Western motivational constructs to the activity theoretical construct of motives. The latter conception comprises three groupings: self-related, cognitive and social motives, as postulated by the activity theorist Lompscher (1999). Set within the qualitative research paradigm, this study utilises case study methodology. Methods of data collection include four interviews for each of the three participants, observations of the participants during two problem-solving sessions, and consequent computer screen analyses of these sessions. The mathematical problems involved the numerical solutions of differential equations using MATLAB. The participants were students studying towards vocational (diploma) qualifications in Mechanical and Electrical Engineering at a comprehensive university in South Africa. My research illustrates the relationship between the expressed needs, motives and goals of the individuals regarding their involvement in the activity of using MATLAB in mathematical learning within a third semester, Mathematics 3 service course.
Keywords: Mathematics; CAS; Activity theory